FAKTOR RISIKO KEJADIAN HIV DAN AIDS PADA REMAJA 14-24 TAHUN - Arfan, Iskandar; Hadisaputro, Suharyo; Anies (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2015)
Abstract. Adolescents are associated with risky activities so as to be a group at risk for HIV infection. Associated with the course of HIV infection, can be understood if the infection usually begins when adolescence. The purpose of this study was to prove the influence of the host and environmental factors that influence the incidence of HIV and AIDS in adolescents 14-24 years of age. The design was used a case-control design and reinforced with qualitative studies with the number of respondents was 110 respondents, including 55 cases and 55 controls, were selected by purposive sampling attention to inclusion and exclusion criteria. Quantitative data were collected by questionare interview, qualitative data were collected by indepth interview. Analysis of bivariate data using a chi-square test and multivariate data using logistic regression. Factor that proved to affect the incidence of infection HIV and AIDS in adolescents 14-24 years is risky behavior (unprotected sex) (OR = 12.41 and 95% CI = 3.37-45.71), the communication of parents (OR = 11 , 66 and 95% CI = 4.24- 32.07). The analysis also shows that if adolescents experience both of the above, then the chances of being infected with HIV and AIDS is equal to (86%). Factors that are not proven effect is education, residency status, risky behaviors (drug injection), the use of media television/handphone (see porn picture or video), the use of the Internet media (see porn picture or video), the condition of the parents (parents of adolescents in the context complete and not divorce or dead), parental supervision, relationship with parents, peer pressure (sex) and pressure peer (injectable drugs). Risk factors for the incidence of HIV and AIDS among adolescents 14-24 years is risky behavior (unprotected sex) high and communications poor parents, Adolescent expected to always understand about (HIV and AIDS, reproductive health, n drug) to avoid unsafe sex and fill leisure time with sports and positive behaviour. Parents / families are also expected to have knowledge about (HIV and AIDS, reproductive health, n drug) establish communication, attention, rules and open to discuss problems of children.